The COVID-19 pandemic and its global effects on dental practice: an international survey - Campus, Guglielmo; Diaz Betancourt, M; Cagetti, MG; Giacaman, RA; Manton, DJ; Douglas, GVA; Carvalho, TS; Carvalho, JC; Vukovic, A; Cortés-Martinicorena, FJ; Bourgeois, D; Machiulskiene, V; et al. (Journal of dentistry, 2021)
Objectives - A multicentre survey was designed to evaluate the impact of COVID-19 outbreak on dental practice worldwide, estimate the COVID-19 related symptoms/signs, work attitudes and behaviour and the routine use of protective measures and Personal Protective Equipment (PPE). - Methods - A global survey using a standardized questionnaire with research groups from 36 countries was designed. The questionnaire was developed and pretested during April 2020 and contained three domains: 1) Personal data; 2) COVID-19 positive rate and symptoms/signs presumably related to the coronavirus; 3) Working conditions and PPE adopted after the outbreak. Countries’ data were grouped by the Country Positive Rate (CPR) during the survey period and by Gross-National-Income per capita. An ordinal multinomial logistic regression model was carried out with COVID-19 self-reported rate referred by dental professionals as dependent variable to assess the association with questionnaire items. - Results - A total of 52,491 questionnaires were returned with a male/female ratio of 0.63. Out of the total respondents, 7,859 dental professionals (15%) reported symptoms/signs compatible with COVID-19. More than half of the sample (n = 27,818; 53%) stated to use FFP2/N95 masks, while 21,558 (41.07%) used eye protection. In the bivariate analysis, CPR and N95/FFP2 were significantly associated (OR = 1.80 95%CI = 1.60/2.82 and OR = 5.20 95%CI = 1.44/18.80, respectively), while Gross-National-Income was not statistically associated with CPR (OR = 1.09 95%CI = 0.97/1.60). The same significant associations were observed in the multivariate analysis. - Conclusions - Oral health service provision has not been significantly affected by COVID-19, although access to routine dental care was reduced due to country-specific temporary lockdown periods. While the dental profession has been identified at high-risk, the reported rates of COVID-19 for dental professionals were not significantly different to those reported for the general population in each country. These findings may help to better plan oral health care for future pandemic events.